Bridging the gap: evaluating emollients and emulsifiers in dermatology for long-term skin health and barrier recovery - Brunina, L. (Medicni Perspektivi, 2025)
This study addresses the significant gap in existing literature regarding the long-term effects of emollients and emulsifiers on skin health to systematically evaluate the impact of these substances on Trans-Epidermal Water Loss (TEWL) and skin barrier functions across various skin conditions. The main aim of this research is to evaluate the effects of commonly used emollients and emulsifiers on skin barrier function across different skin conditions to provide insights that will contribute to the development of optimized skincare formulations for individuals with compromised skin barriers. A literature search was conducted across multiple databases, including PubMed, Scopus, Web of Science, and Google Scholar, using targeted search strings to gather relevant studies published over the last 20 years. The inclusion criteria focused on peer-reviewed studies that provided empirical data on the effects of emollients and emulsifiers on TEWL and skin barrier functions, specifically in human subjects. A total of 88 articles were initially identified, with 41 meeting the strict inclusion criteria after quality assessment using Joanna Briggs Institute checklists. The review revealed varied effects of emollients and emulsifiers on skin health. Natural oils were found to enhance skin barrier functions and reduce TEWL, whereas synthetic emollients raised concerns about their occlusive properties and potential to worsen skin conditions over time. Emulsifiers showed dual effects; some exacerbated TEWL in normal skin but reduced it in damaged skin, highlighting the complexity of their interaction with skin barrier components. The findings emphasize the need for standardized research methodologies and long-term studies to better understand the mechanisms by which emollients and emulsifiers influence skin health, particularly regarding TEWL measurement techniques while products do exhibit dual behavior and scientific evidence should guide the selection of emulsifiers and emollients in skincare products to ensure both efficacy and long-term safety as well as the special assessment of the safer alternative what support both human health and environmental sustainability.